Analysis of financial and tax impact from the valuation of inventories under IFRS in the company VETNAR SA - Jazmin Abigail Coronel Morocho; Cecilia Ivonne Narváez Zurita; Juan Carlos Erazo Álvarez (Revista Arbitrada Interdisciplinaria Koinonía, 2019)
The following research aims to design the appropriate procedures for the valuation of inventories under IFRS for SMEs in the company VETNAR SA of the Naranjal canton, province of Guayas, in order to improve the reliability of balance sheet information and determine the financial impact and tax. The application of the IFRS for SMEs, empowers the company to prepare and present the financial statements with real and reasonable information, allowing to recognize the accounting treatment of the inventory, and the amount of the cost, as an asset. In addition, these inventory valuation procedures will provide information on the rotation of each product and the profit margin.